Evaluation of statin utilization in the Republic of Macedonia during 2013–2016 - Naumovska Z; Nestorovska AK; Grozdanova A; Hristova K; Dimovski A; Suturkova L; Sterjev Z (Dove Medical Press, 2018)
Zorica Naumovska,1 Aleksandra K Nestorovska,1 Aleksandra Grozdanova,1 Kristina Hristova,2 Aleksandar Dimovski,1 Ljubica Suturkova,1 Zoran Sterjev1 1Department of Pharmaceutical Chemistry, Faculty of Pharmacy, SS “Cyril and Methodius”, Skopje, Republic of Macedonia; 2Department of Health Insurance Fund of R. Macedonia, Skopje, Republic of Macedonia Purpose: A rational use of statins has a major and increasing importance in public health and allocation of financial resources by the health insurance funds (HIFs). The aim of this study was to evaluate the market share and utilization trends of statins in the Republic of Macedonia (R. Macedonia) from 2013 to 2016. Materials and methods: A retrospective analysis and data comparison for the utilization of HMG-CoA inhibitors (C10AA) in R. Macedonia from 2013 to 2016 were conducted. The data obtained from HIF, IMS Health, pharmaceutical industry and marketing authorization holders (MAHs) were evaluated through defined daily doses per 1000 insurers per day (DDD/TID). Results: Cardiovascular drugs are the most commonly prescribed and utilized drugs in R. Macedonia. The HIF cost for cardiovascular disease (CVD) increased to €2,243,777.00 in the period from 2013 to 2016. Since 2012, the reimbursement shows that atorvastatin accounts for the highest expenditure reaching €2,162,958.00 while rosuvastatin reached €1,645,860.00 in 2016. The increased consumption of statins is confirmed from the records obtained from IMS Health databases in the evaluated period in R. Macedonia suggesting increased expenditures with total growth of 35.65% reaching €4,421,280.24 in 2016. Evident growth of statin consumption is confirmed from the data obtained from the pharmaceutical industry and MAH. The statin use increased from 42.347 DDD/TID in 2013 to 71.697 DDD/TID in 2016, although it is lower in comparison to other European Union (EU) countries (1.1–2.5-fold). Conclusion: The rapid increase in the consumption of statins can be attributed mostly to an increase in the consumption volume. It is inevitable to widen the price reduction concept with initiatives that may control statin consumption amounts with measures such as educational programs for rational drug utilization and targeting eligible population. Keywords: statins, cardiovascular prevention, expenditures for statin utilization prescription drug expenditure